Hierarki Kebutuhan Tokoh dalam Film Miracle in Cell Nomor 7 Perspektif Psikologis Humanistik Abraham Maslow: Hierarchy of Needs of Characters in the Film Miracle In Cell Number 7 Humanistic Psychological Perspective of Abraham Maslow - Rahma Novia Budiati; Sucipto Sucipto; Imayah Imayah (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2026)
This study aims to analyze the dynamics of the characters' hierarchy of needs in the film Miracle in Cell Number 7 through the perspective of Abraham Maslow's humanistic psychology. The film depicts the struggle of a father with intellectual disabilities who faces legal injustice while trying to maintain an emotional relationship with his daughter. This study uses a descriptive qualitative approach, employing content analysis of scenes, dialogue, and character expressions to represent the five levels of needs in Maslow's theory: physiological needs, safety, love and belonging, esteem, and self-actualization. The research data were obtained from the Indonesian version of the film Miracle in Cell Number 7 by Hanung Bramantyo and analyzed through coding, need classifications, and psychological interpretation of the characters. The results show that the need for love and belonging is the most dominant factor in shaping the main character's behavior and psychological resilience. Although the need for safety is not fully met due to legal pressure and social stigma, the character still maintains a sense of meaning in life, compassion, and self-esteem. In addition, the fulfillment of the character's needs is influenced by both internal factors, such as personality traits and intellectual limitations, and external factors, such as social support and environmental conditions. These findings indicate that the hierarchy of needs is flexible and contextual. Hence, a humanistic psychology approach is relevant for understanding the complexity of motivation and the psychological dynamics of the film's characters.